Colon cancer surgery in patients operated on an emergency basis - Ramos,Rodrigo Felippe (2017)
ABSTRACT Objective: to study the epidemiological profile of patients with colorectal cancer operated on an emergency basis at the Bonsucesso Federal Hospital. Methods: this is a retrospective study of patients operated between January 1999 and December 2012. We analyzed the following variables: age, gender, clinical data, TMN staging, tumor location, survival and types of surgery. Results: we evaluated 130 patients in the study period. The most frequent clinical picture was intestinal obstruction, in 78% of cases. Intestinal perforation was the surgical indication in 15%. The majority (39%) of the patients had advanced TNM staging, compared with 27% in the initial stage. There were 39 deaths (30%) documented in the period. The most common tumor site was the sigmoid colon (51%), followed by the ascending colon (16%). The curative intent was performed in most cases, with adjuvant treatment being performed in 40% of the patients. Distant metastases were found in 42% of the patients and 10% had documented disease recurrence. Disease-free survival at two and five years was 69% and 41%, respectively. Conclusion: there was a high mortality rate and a low survival rate in colorectal cancer patients operated on urgently.